Problems of managing process of ensuring economic security - V. P. Shpaltakov (Омский научный вестник: Серия "Общество. История. Современность")
The main problems of the state of the Russian economy, which give rise to serious threats to economic security, are considered. The topic is relevant due to the growing risks and threats to our economy. The purpose of the article is to analyze the nature and methods of state management of conditions affecting the level of economic security in the country. The tasks of the analysis are to identify deficiencies in the management system and ways to eliminate them. The novelty of the article consists in a comprehensive analysis of the main reasons and factors of the growing danger for the intensification of stagnation and the economy lagging behind the advanced countries. The main weaknesses and shortcomings of state management of the process of ensuring economic security are revealed: the growth of bureaucracy, corruption, the preservation of a backward resource-export model of the economy. A number of necessary reforms of the state apparatus and diversification of economies are proposed